Analysis of Adjudicative Authority in Regional Election Disputes: A Case Study of the Cianjur Regency Regional Election Dispute Based on Law Number 10 of 2016 and Its Amendments on the Election of Governors, Regents, and Mayors - Sinaga, Dahman; Nuraeni, Yeni; Sihombing, Lasmin Alfies (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
The administration of regional head elections (Pilkada), as a manifestation of popular sovereignty, requires a dispute resolution mechanism that ensures justice and legal certainty. However, Law No. 10 of 2016 distributes dispute resolution authority among several institutions, which in practice creates the potential for jurisdictional conflicts. This study examines the problem of overlapping authority between the General Courts in handling electoral criminal offenses and the Constitutional Court in resolving disputes over Pilkada results. The objective of this research is to analyze juridically the source of the conflict of authority and its impact on legal certainty, with a case study of the Cianjur Regency Pilkada. The findings indicate that the fragmented attribution of authority under Law No. 10 of 2016 does not provide a synchronization mechanism between criminal judgments that have obtained permanent legal force (inkracht) and decisions on election result disputes (PHPU) that are final and binding. This condition produces a dualism of contradictory legal truths between the District Court and the Constitutional Court. Consequently, it leads to legal uncertainty and the potential delegitimization of Pilkada results. This study recommends the establishment of a specialized Pilkada court to comprehensively integrate all dispute resolution regimes.